'Only cuppa tea Christians': colonisation, authentic indigeneity and the missionary linguist. Issue 2 (2nd April 2016) - Rademaker, Laura
Abstract: 'Cuppa tea Christians' were Aboriginal people whose faith was supposedly only as deep as their desire for a cuppa. At the Church Missionary Society of Australia's Angurugu mission to Anindilyakwa people in the Northern Territory, missionaries in the 1960s suspected that most 'conversions' were only shallow. This article examines the long association in English speakers' minds of Aboriginal cultures with insincerity or fakery. I argue that the prevalence of Anindilyakwa 'backsliding' at the mission in the 1960s pushed missionaries to search for new approaches to know for sure who, if anyone, was sincerely converted. Language became the key for missionaries to speak directly to Aboriginal hearts and know the Aboriginal mind, based on an assumption that Aboriginal people were only authentic when speaking their own languages. Although missionary linguistic projects tended towards impulses to 'colonise Indigenous consciousness', Anindilyakwa people managed this project, as well as working out their own diverse responses to the missionaries' gospel. This article has been peer reviewed.